STAT3 Activates miR-155 in Th17 Cells and Acts in Concert to Promote Experimental Autoimmune Uveitis - Escobar, Thelma (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. MicroRNA-155 (miR-155) and STAT3 are implicated in uveitis and pathogenic mechanisms of CNS autoimmune diseases. In our study, we used miR-155(−/−) mice and mice with targeted STAT3 deletion in T cells (CD4-STAT3KO) to investigate roles of miR-155 and STAT3 in the development of experimental autoimmune uveitis (EAU), a mouse model of human uveitis. METHODS. We induced EAU in WT, miR-155(−/−), or CD4-STAT3KO mice by immunization with interphotoreceptor retinoid-binding protein/complete Freund's adjuvant (IRBP/CFA) or adoptive transfer of T cells. EAU was assessed by funduscopy and histology. RNA expression was analyzed by quantitative PCR (qPCR), while cytokine production was assessed by fluorescence-activated cell sorting (FACS). RESULTS. We used a combination of genomic and genetic tools to provide the first evidence that STAT3 binds directly to the miR-155 locus and that STAT3 is required for miR-155 expression. Furthermore, STAT3-dependent increase in miR-155 expression in vivo correlated temporally with onset of EAU, and miR-155(−/−) or CD4-STAT3KO mice did not suffer EAU. CD4(+) lymph node cells from IRBP-immunized WT mice transferred EAU to naïve wild-type (WT) and miR-155(−/−) mice, while miR-155(−/−) IRBP-specific T cells did not. CONCLUSIONS. Although miR-155 and STAT3 have been implicated in the etiology of multiple sclerosis (MS), uveitis, or rheumatoid arthritis, their exact roles in these diseases are unclear. We show here for the first time to our knowledge that STAT3 regulates miR-155 expression in Th17 cells. We show further that STAT3 and miR-155 form an axis that promotes the expansion of pathogenic Th17 cells that mediate uveitis. Thus, STAT3 and miR-155 may be therapeutic targets for treating uveitis and other Th17-mediated inflammatory disorders.